2000
DOI: 10.1159/000045713
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Seroresponse to Influenza Vaccination in Dialysis Patients

Abstract: Background: Hemodialysis (HD) patients are immunocompromised, and they have been shown to react suboptimally to recommended vaccinations. Advances in dialysis therapy and other supportive measures may theoretically result in better immune system functions. Clinical evidence supporting this theory has, however, not been presented. With influenza vaccination response, we tried to address this question. Methods: 42 HD and 15 continuous ambulatory peritoneal dialysis (CAPD) patients were vaccinated with a trivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 17 publications
1
38
1
1
Order By: Relevance
“…51,52 Finally, the strategy of vitamin D supplementation or use as a vaccine adjuvant needs to be explored further, instead of merely optimizing "homeostatic" 25-(OH) D status. [10][11][12][13]26,53,54 Several studies involving mature adult mice that were immunized subcutaneously or intramuscularly with inactivated vaccine (inactivated polio vaccine, 53 Haemophilus influenzae type b oligosaccharide conjugated to diphtheria toxoid vaccine, 54 and hepatitis B surface antigen (HBsAg) 55 ), co-administered with 1,25-(OH) 2 D3 demonstrated production of antigen-specific mucosal immunity (IgA and IgG antibodies), as well as enhanced systemic immune responses. It is likely that vitamin D is not an independent predictor of a binary outcome, but may be influential through its complex immune physiological interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 Finally, the strategy of vitamin D supplementation or use as a vaccine adjuvant needs to be explored further, instead of merely optimizing "homeostatic" 25-(OH) D status. [10][11][12][13]26,53,54 Several studies involving mature adult mice that were immunized subcutaneously or intramuscularly with inactivated vaccine (inactivated polio vaccine, 53 Haemophilus influenzae type b oligosaccharide conjugated to diphtheria toxoid vaccine, 54 and hepatitis B surface antigen (HBsAg) 55 ), co-administered with 1,25-(OH) 2 D3 demonstrated production of antigen-specific mucosal immunity (IgA and IgG antibodies), as well as enhanced systemic immune responses. It is likely that vitamin D is not an independent predictor of a binary outcome, but may be influential through its complex immune physiological interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have included subjects already on vitamin D supplementation. [9][10][11][12][13] Epidemiological studies have demonstrated a higher incidence of vitamin D deficiency in elderly and obese populations. 14,15 Recent findings from a longitudinal study of older adults suggest leptin may mediate obesity-related vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative detection of antibodies against the (H1N1)v was performed by a hemagglutination inhibition test modified from Kendal et al Briefly, after treatment with receptor destroying enzyme (RDE), two-fold We found the response to vaccination was similar in hemodialysis and peritoneal dialysis patients, as was also found in another study. 28 It has been suggested that the immune response in PDPs is better than that of HDs because continuous ambulatory peritoneal dialysis improves the clearance of middle molecules. 15 Different parameters influence the response to the (H1N1)v vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…Hay que resaltar que cerca del 20% de las mujeres que se dializan en nuestro centro y con criterio de screening de cáncer de mama y cérvix, no se han hecho ninguna mamografía ni citología cervicovaginal, datos que se asemejan a los observados en otros estudios (7) . Las infecciones en los pacientes en diálisis revisten mayor gravedad y a pesar de la baja respuesta que los pacientes con insuficiencia renal crónica manifiestan ante las vacunaciones, se ha demostrado la efectividad de éstas (8) . La importancia de las inmunizaciones reside en lograr la prevención de la enfermedad a través de la vigilancia epidemiológica e inmunización efectiva, y no tenemos que olvidar que las vacunas constituyen una de las actividades preventivas más eficientes.…”
Section: Materials Y Métodosunclassified